A resolute man - Greenwood, Leigh (Sourcebooks Casablanca, 2020)
"The Randolph brothers are known as a wild, unruly bunch. Carving an empire out of the rugged Texas land, fighting off rustlers, they're unwilling to change their ways until oldest brother George Randolph lays down the law. George wants to bring his brothers in line and put his ranch in order, but he needs to find someone strong enough to help him. Rose Thornton is penniless and desperate, and will do just about anything to keep going. It's going to take grit for her to help George tame this frontier."--Provided by publisher.